Quality of life and service satisfaction in outpatients with severe or non-severe mental illness diagnoses - Ådnanes, M; Kalseth, J; Ose, S; Ruud, T; Rugkåsa, J; Puntis, S (Springer International Publishing, 2018)
Purpose Our study investigated quality of life (QoL) in patients with severe or non-severe mental illness diagnoses (SMI and non-SMI) and the association between QoL and service satisfaction measured as patients’ perception of continuity of care (CoC), therapeutic relationship, and unmet service needs. Methods We conducted a national cross-sectional survey among 3836 mental health outpatients, of whom 1327 (34.6%) responded. We assessed QoL with the Manchester Short Assessment of Quality of Life (MANSA), CoC with the CONTINUUM, the therapeutic relationship with the Therapeutic Relationship in Community Mental Health Care (STAR-P) and developed a simple scale to measure unmet service needs. Results Outpatients with SMI (n = 155) reported significantly better QoL than those with non-SMI (n = 835) (p = 0.003). In both groups, QoL was positively associated with cohabitation (p = 0.007 for non-SMI and p = 0.022 for SMI), good contact with family and friends (p < 0.001 for both) and positive ratings of CoC (p < 0.001 for non-SMI and p = 0.008 for SMI). A positive association between QoL and therapeutic relationship (p = 0.001) and a negative association between QoL and unmet needs for treatment (p = 0.009) and activity (p = 0.005) was only found in the non-SMI group. Conclusion Our study highlights the important differences between those with SMI and those with non-SMI in their reported QoL and in the relationship between QoL and service satisfaction, with only non-SMI patients’ QoL influenced by the therapeutic relationship and unmet needs for treatment and activity. It also shows the importance of continuity of care and social factors for good QoL for both groups.